Effect of Si and Cr on formation of aluminide coatings on Ti6Al4V alloy by low temperature aluminizing: Wear and oxidation behavior - Doleker, Kadir Mert; Yener, Tuba; Erdogan, Azmi; Yilmaz, Ferhat; Efe, Gozde Celebi; Erdoğan, Azmi (Elsevier Science Sa, 2025)
To improve the surface properties of the Ti-6Al-4 V titanium alloy, TiAl3-based intermetallic coatings were produced at 710 degrees C-4 h via a low-temperature aluminizing process. Additionally, Si and Cr were incorporated into the Ti-Al coating to investigate their effects on the properties of the Ti-Al system. The findings revealed that the coatings formed strong metallurgical bonds with the substrate, and no significant cracks were detected in the Ti-Al system coatings. However, the addition of Cr was found to have a negative effect on the growth of the coating layer. Similarly, the simultaneous addition of Cr and Si reduced the thickness of the layer from 14 mu m to 5 mu m. An increase of up to 248 GPa elastic modulus (EIT) and 10.36 GPa hardness was achieved with the aluminide coating of Ti6Al4V, which have had 150 GPa EIT and 5.56 GPa hardness. While all coatings provided better wear performance compared to the substrate, the lowest volume loss was observed in the TiAl coating with the highest thickness. Similarly, the best oxidation resistance was obtained in TiAl due to higher coating thickness and lower phase transformation in its coating layer compared to others. The addition of Si and Cr did not affect the formed oxide products, but they decreased the oxidation resistance due to thinner coating structure.
Keywords: Ti6al4v; Aluminizing; Nano Indentation; Wear; Oxidation